Negative electrode, method for manufacturing same, non-aqueous electrolyte secondary battery comprising
By combining metal-based and carbon-based active material particles in the negative active material layer of the nonaqueous electrolyte secondary battery and optimizing the distribution of carbon nanotubes, the problem of degradation of the cycle characteristics of the secondary battery is solved, and the excellent cycle characteristics and stable performance of the battery are achieved.
Patent Information
- Application Number
- CN202411480063.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-24
- Filing Date
- 2024-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
The conductivity of metal-based active substance particles such as SiOx is low, resulting in a decrease in the circulation characteristics of the secondary battery. Even if a good conductive path is formed using carbon nanotubes, it is difficult to maintain excellent circulation characteristics of the secondary battery.
In the negative electrode active material layer of the nonaqueous electrolyte secondary battery, metal-based active material particles and carbon-based active material particles are combined, and the average length of the carbon nanotube is determined to be 1.5 μm or more by scanning transmission electron microscope images. The surface of the active material particles is covered with a first binder not mixed with the carbon nanotube, and the active material layer includes the first carbon nanotube attached to the first binder in a manner covering the first binder and the second carbon nanotube mounted between the two active material particles.
By optimizing the structure of the negative electrode active material layer, the circulation characteristics of the secondary battery are significantly improved, ensuring the stability and performance of the battery during the charging and discharging process.
Smart Images

Figure CN119890227A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode and a method for producing the same, and a nonaqueous electrolyte secondary battery including the negative electrode and a method for producing the same. Background Art
[0002] The non-aqueous electrolyte secondary battery has a negative electrode including an active material layer. The active material layer may contain active material particles such as graphite and SiOx and fibrous carbon such as carbon nanotubes (for example, Japanese Patent Application Laid-Open No. 2021-99955). Summary of the invention
[0003] As for metal active material particles such as SiOx, compared with graphite, the conductivity is low, and the expansion and contraction associated with the charging and discharging of the secondary battery is large, so the conductive path formed between the active material particles around is deteriorated, which easily causes the reduction of the cycle characteristics of the secondary battery. As for carbon nanotubes, a good conductive path can be formed by bridging between the active material particles, so they are used to suppress the deterioration of the above-mentioned conductive path. However, even when the active material layer contains carbon nanotubes, the cycle characteristics of the secondary battery are sometimes reduced.
[0004] An object of the present disclosure is to provide a negative electrode capable of obtaining a secondary battery having excellent cycle characteristics and a method for producing the same, and a nonaqueous electrolyte secondary battery including the negative electrode and a method for producing the same.
[0005] [1] A negative electrode, which is a negative electrode for a non-aqueous electrolyte secondary battery,
[0006] The invention comprises: an active material layer including active material particles, carbon nanotubes and a first binder,
[0007] The active material particles include metal active material particles and carbon active material particles.
[0008] The average length of the carbon nanotubes determined by analysis of a scanning transmission electron microscope image of the active material layer is 1.5 μm or more,
[0009] At least a portion of the first binder covers at least a portion of the surface of the active material particle in a state where the first binder is not mixed with the carbon nanotubes.
[0010] The carbon nanotubes include: first carbon nanotubes attached to the first binder in a manner of covering the first binder, and second carbon nanotubes bridged between the two active material particles, wherein the first binder covers the surface of the active material particles without being mixed with the carbon nanotubes.
[0011] [2] The negative electrode according to [1], wherein the ratio of the carbon nanotubes not mixed with the first binder relative to the total amount of the carbon nanotubes in the active material layer, as determined by analysis of the scanning transmission electron microscope image of the active material layer, is greater than 60%.
[0012] [3] The negative electrode according to [1] or [2], wherein the metal-based active material particles include particles of one or more selected from Si, SiOx, and a composite of Si and C.
[0013] [4] The negative electrode according to any one of [1] to [3], wherein the metal-based active material particles include particles of a composite of Si and C.
[0014] [5] The negative electrode according to any one of [1] to [4], wherein the carbon nanotube is a single-walled carbon nanotube.
[0015] [6] The negative electrode according to any one of [1] to [5], wherein the carbon nanotube has a G / D ratio of 80 or less.
[0016] [7] The negative electrode according to any one of [1] to [6], wherein the first binder is at least one of carboxymethyl cellulose and polyacrylic acid.
[0017] [8] The negative electrode according to [7], wherein the active material layer contains a second binder different from the first binder,
[0018] The second adhesive includes styrene butadiene rubber.
[0019] [9] A non-aqueous electrolyte secondary battery comprising the negative electrode according to any one of [1] to [8].
[0020]
[10] A method for producing a negative electrode, which is a method for producing a negative electrode for a non-aqueous electrolyte secondary battery.
[0021] The method comprises a first step of preparing a slurry, and a second step of using the slurry to form an active material layer of the negative electrode.
[0022] The slurry includes active material particles, a first binder, carbon nanotubes, and water.
[0023] The active material particles include metal-based active material particles and carbon-based active material particles.
[0024] The above-mentioned first step includes: a step (1a) of obtaining a first mixed body by kneading the above-mentioned active material particles, the above-mentioned first binder, and water in a solid content range of 60 to 65 weight %; a step (1b) of obtaining a second mixed body by adding water to the above-mentioned first mixed body and kneading in a solid content range of less than 50 weight %; and a step (1c) of obtaining a third mixed body by kneading the above-mentioned second mixed body and the above-mentioned carbon nanotubes.
[0025]
[11] The method for producing a negative electrode according to
[10] , wherein the first binder is at least one of carboxymethyl cellulose and polyacrylic acid,
[0026] The first step further comprises a step of kneading the third kneaded body with a second binder.
[0027] The second adhesive includes styrene butadiene rubber.
[0028]
[12] A method for manufacturing a negative electrode according to
[10] or
[11] , wherein the step (1a) comprises: a step of dry-mixing the active material particles and the first binder to obtain a mixture; and a step of kneading the mixture and water in a solid content range of 60 to 65% by weight.
[0029]
[13] The method for producing a negative electrode according to any one of
[10] to
[12] , wherein the metal-based active material particles include particles of one or more selected from Si, SiOx, and a composite of Si and C.
[0030]
[14] The method for producing a negative electrode according to any one of
[10] to
[13] , wherein the first binder is at least one of carboxymethyl cellulose and polyacrylic acid.
[0031]
[15] The method for producing a negative electrode according to any one of
[10] to
[14] , wherein the G / D ratio of the carbon nanotubes is 80 or less.
[0032]
[16] A method for producing a non-aqueous electrolyte secondary battery, comprising: a step of producing a negative electrode using the method for producing a negative electrode according to any one of
[10] to
[15] .
[0033] The foregoing and other objects, features, aspects and advantages of the present invention will become more apparent from the following detailed description of the present invention when read in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is an explanatory diagram schematically showing an example of the state in the active material layer of the negative electrode according to the embodiment.
[0035] Figure 2 This is an explanatory diagram schematically showing an example of the state in the active material layer of the negative electrode produced by the steps described in the comparative example.
[0036] Figure 3 It is a flowchart which shows the manufacturing method of the negative electrode which concerns on embodiment.
[0037] Figure 4 This is a scanning transmission electron microscope image of the surface of the active material layer of the negative electrode obtained in Example 1.
[0038] Figure 5 This is a scanning transmission electron microscope image of the surface of the active material layer of the negative electrode obtained in Example 2.
[0039] Figure 6 This is a scanning transmission electron microscope image of the surface of the active material layer of the negative electrode obtained in Comparative Example 1.
[0040] Figure 7 This is a scanning transmission electron microscope image of the surface of the active material layer of the negative electrode obtained in Comparative Example 2. DETAILED DESCRIPTION
[0041] In this specification, as for the numerical range such as "x to y", unless otherwise specified, it includes the upper limit and the lower limit. That is, "x to y" means a numerical range of "above x and below y". A numerical value arbitrarily selected from the numerical range can be set as a new upper limit or lower limit. For example, a new numerical range can be set by arbitrarily combining a numerical value within the numerical range with a numerical value recorded in another part, table, or figure in this specification.
[0042] (negative electrode)
[0043] Figure 1 It is an explanatory diagram schematically showing an example of the state in the active material layer of the negative electrode according to the embodiment. Figure 2 This is an explanatory diagram schematically showing an example of the state in the active material layer of the negative electrode produced by the steps described in the comparative example.
[0044] The negative electrode of the present embodiment (hereinafter also referred to as "the present negative electrode") is a negative electrode for a non-aqueous electrolyte secondary battery (hereinafter also referred to as a "secondary battery"), and includes an active material layer. The active material layer includes active material particles, carbon nanotubes (hereinafter also referred to as "CNTs"), and a first binder. The active material particles include metal-based active material particles (hereinafter also referred to as "metal-based particles") and carbon-based active material particles (hereinafter also referred to as "carbon-based particles"). The average length of the CNTs obtained by analyzing the scanning transmission electron microscope image (hereinafter also referred to as "SEM image") of the active material layer is greater than 1.5 μm. At least a portion of the first binder covers at least a portion of the surface of the active material particles in a state where it is not mixed with the CNTs. The CNTs include: a first carbon nanotube (hereinafter also referred to as "the first CNT") attached to the first binder in a manner that covers the surface of the first binder that covers the surface of the active material particles in a state where it is not mixed with the CNTs, and a second carbon nanotube (hereinafter also referred to as "the second CNT") that is bridged between two active material particles.
[0045] The present negative electrode may have an active material layer on a negative electrode current collector. The active material layer may be formed on only one side of the negative electrode current collector or may be formed on both sides. The negative electrode current collector is, for example, a metal foil made of a copper material such as copper or a copper alloy.
[0046] The active material layer includes active material particles 1 at least a portion of which is covered with a first binder 2. Figure 1 ). The first binder 2 can be directly attached to the surface of the active material particle 1. As for the active material particle 1, it is sufficient as long as at least a portion of the entire surface of the active material particle 1 is covered by the first binder 2. For example, the first binder 2 can be dispersed on the entire surface of the active material particle 1, and the first binder 2 can exist on the entire surface of the active material particle 1.
[0047] The first binder 2 covering the active material particles 1 includes at least a first binder that is not mixed with CNT3 (hereinafter also referred to as "first binder (s)"), and may also include a first binder that is mixed with CNT3 (hereinafter also referred to as "first binder (m)"). When the first binder 2 includes the first binder (m), in the SEM image of the surface of the active material layer, the area occupied by the first binder (s) is preferably larger than the area occupied by the first binder (m). In this specification, in the SEM image of the surface of the active material layer, all CNTs existing on the surface and inside of the first binder are determined, and when the total area of the CNTs not covered by the first binder and the total area of the CNTs covered by the first binder are calculated, the area of the first binder in which the ratio of the former to the sum of the former and the latter is more than 80% is set as the first binder (s), and the area of the first binder less than 20% is set as the first binder (m).
[0048] In the active material layer, the first CNT 31 is attached to the first binder (s) in a manner of covering the surface of the first binder (s) covering the active material particles 1 ( Figure 1 ). As for the first CNT31, the entire length direction can be attached to the first binder (s), and a part of the length direction can be attached to the first binder (s). In this specification, the first CNT31 is a CNT in which more than 80% of its total length exists on the surface of the first binder (s), and refers to CNTs other than the second CNT32. The proportion of the first CNT31 relative to all CNTs in the active material layer is large. It is taught that: when preparing a slurry for forming the active material layer, the slurry is prepared under conditions where the first binder and CNT are difficult to mix. As such conditions, for example, the solid content concentration when the first binder and CNT are mixed is relatively small as described in the manufacturing method described later.
[0049] In the active material layer, the second CNT 32 is bridged between two active material particles 1 ( Figure 1 ). Both ends of the second CNT 32 can be directly connected to the surface of the two active material particles 1 or the surface of the first binder 2 covering the active material particles 1. Since the average length of the CNT contained in the active material layer is 1.5 μm or more, it is easier to form a good conductive path between the active material particles 1 compared to the second CNT 32. As a result, the secondary battery using the present negative electrode can have excellent cycle characteristics.
[0050] The active material layer including the first CNT and the second CNT can be obtained by adjusting the order of mixing the CNTs, the solid content concentration when mixing the CNTs, and other conditions when preparing the slurry used to form the active material layer (described later). The active material layer including the first CNT and the second CNT can be obtained by using a slurry prepared by a process of mixing a mixed body including active material particles and a first binder in a state with a relatively small solid content and CNTs, as described in the embodiments described later.
[0051] In contrast to the above, as described in the comparative example below, when the active material layer is obtained by using a slurry prepared by a process of kneading active material particles, a first binder, and CNTs at a relatively high solid content, it is difficult to obtain an active material layer containing the first CNT and the second CNT. Figure 2 As shown in FIG, it is easy to obtain a mixture of CNT 3 and the first binder 2 covering the surface of the active material particles 1 and an active material layer built between two active material particles 1. Figure 2 In the active material layer shown in FIG. , a small proportion of the CNT surface is exposed on the surface of the first binder 2 , and a large proportion of the CNT 3 surface is covered with the first binder 2 .
[0052] The CNTs contained in the active material layer may include third carbon nanotubes (third CNTs) attached to the first binder (m) so as to cover the surface of the first binder (m) covering the active material particles.
[0053] The ratio of CNTs not mixed with the first binder relative to the total amount of CNTs in the active material layer (hereinafter also referred to as "CNT ratio") is preferably greater than 60%, more preferably greater than 70%, further preferably greater than 80%, and can be greater than 85%. The CNT ratio is preferably greater than 60% and less than 100%, can be 70 to 99%, and can be 80 to 95%. By having the CNT ratio within the above range, a good conductive path can be formed between the active material particles, thereby improving the cycle characteristics of the secondary battery. As for the CNT ratio, it can be determined by analyzing the SEM image of the active material layer as described in the embodiments described later.
[0054] Examples of a method for adjusting the CNT ratio to the above ratio include a method of adjusting conditions such as the solid content concentration when mixing the CNT when preparing the slurry used to form the active material layer.
[0055] The active material layer includes active material particles for the negative electrode. The active material particles include metal particles and carbon particles, and may include active material particles other than metal particles and carbon particles. The total content of carbon particles and metal particles contained in the active material particles may be 90 to 100 weight percent, 90 to 99 weight percent, or 92 to 95 weight percent relative to the total amount of active material particles. The ratio of carbon particles to metal particles in the active material particles may be 70:30 to 95:5, 80:20 to 92:8, or 85:15 to 95:5.
[0056] When the active material layer is formed on both sides of the negative electrode current collector, the mass per unit area of the active material layer on both sides (both sides in total) can be, for example, 150 to 250 g / m 2 , can be 170~230g / m 2 , can be 180~210g / m 2 . The mass per unit area of each single side of the negative electrode collector can be set to, for example, half of the mass per unit area of each of the two sides mentioned above. The thickness of each single side of the active material layer can be, for example, 90 to 200 μm, 100 to 180 μm, or 120 to 150 μm. The packing density of the active material layer can be calculated by the following formula, and can be, for example, 1.3 to 1.9 g / cc, 1.4 to 1.8 g / cc, or 1.5 to 1.7 g / cc.
[0057] Packing density [g / cc] = mass per unit area of active material layer [g / m 2 ] / Thickness of active material layer [μm]
[0058] The metal particles include particles of metal elements such as metal simple substances or metal oxides containing elements selected from silicon (Si), tin (Sn), antimony (Sb), bismuth (Bi), titanium (Ti), and germanium (Ge). The metal particles preferably include one or more particles selected from Si, SiOx (x = 0.5 to 1.5), a composite of Si and C (hereinafter also referred to as "SiC composite"), and Sn, or one or more particles selected from the group, more preferably one or more particles selected from Si, SiOx, and SiC composites. The metal particles are further preferably SiC composite particles. For example, a SiC composite is a composite in which Si is dispersed in a carbon matrix.
[0059] The carbon-based particles preferably include one or more particles selected from carbon materials such as graphite, hard carbon, soft carbon, and amorphous coated graphite, or are one or more particles selected from the group, preferably include graphite particles or are graphite particles. The average particle size D50 of the graphite particles can be 5 to 25 μm, 8 to 23 μm, or 10 to 20 μm. The average particle size D50 in this specification is the particle size at which the accumulation of frequencies from the smaller particle size in the volume-based particle size distribution becomes 50%. The volume-based particle size distribution can be measured by a laser diffraction particle size distribution measuring device. The specific surface area (BET) of the graphite particles can be 1.0 m 2 / g or more and 3.0m 2 / g or less, can be 1.2m 2 / g or more and 2.5m 2 The specific surface area can be calculated by the BET multipoint method from an adsorption isotherm measured by a gas adsorption method using a fully automatic specific surface area meter or the like.
[0060] CNT may be a single-walled carbon nanotube (hereinafter also referred to as "SWCNT") or a multi-walled carbon nanotube such as a double-walled carbon nanotube (DWCNT). SWCNT is preferred from the viewpoint of easily obtaining CNTs with few defects in the CNT structure and a high G / D ratio.
[0061] The average length of the CNTs in the active material layer is 1.5 μm or more, 1.6 μm or more, 1.7 μm or more, 1.8 μm or more, 1.9 μm or more, or 2.0 μm or more. The average length of the CNTs may be 1.5 to 5.0 μm, 1.8 to 3.0 μm, or 2.0 to 2.5 μm. As for the average length of the CNTs, it can be determined by analyzing the SEM images as described in the embodiments described later. It is believed that by the presence of CNTs of the above average length in the active material layer, a good conductive path can be formed between the active material particles, which can improve the cycle characteristics of the secondary battery.
[0062] The G / D ratio of CNT can be 80 or less, 70 or less, 50 or less, preferably 30 or less, and 20 or less. The G / D ratio of CNT can be 5 to 80, 10 to 50, or 10 to 30. The G / D ratio is a value obtained by Raman spectroscopic analysis. In the Raman spectrum of CNT, the wavelength at 1590 cm -1 The Raman shift found nearby is called the G band from graphite and will be at 1350 cm -1The Raman shift found near is called the D band from defects in amorphous carbon and graphite. It can be said that the larger the G / D ratio of the CNT, the higher the crystallinity and the greater the strength. In order to form an active material layer as described later, when a slurry containing CNTs, active material particles and a first binder is used, if a strong shear force is applied to improve the dispersibility of the CNTs to mix the above components, the length of the CNTs sometimes becomes shorter due to the CNTs being chopped, etc. However, in the present embodiment, when preparing the slurry as described later, the timing of adding the CNTs is adjusted, so that even when using CNTs with a small G / D ratio (small strength), the length of the CNTs can be suppressed from being shortened. As a result, a good conductive path can be formed between the active material particles, thereby improving the cycle characteristics of the secondary battery. With respect to the G / D ratio in this specification, it is the ratio of 1550 to 1650 cm in the Raman spectrum of the CNT. -1 The maximum peak intensity in the range of 1300 to 1400 cm -1 The maximum peak intensity in the range of is calculated as D. The G / D ratio of CNT can be determined by the procedure described in the examples below.
[0063] The content of CNT in the active material layer may be 0.01 to 1 part by weight, 0.05 to 0.1 part by weight, or 0.1 to 0.5 part by weight relative to 100 parts by weight of the active material particles.
[0064] As for the first binder, one or more selected from cellulose-based binders such as carboxymethyl cellulose (hereinafter also referred to as "CMC"), methyl cellulose (hereinafter also referred to as "MC"), hydroxypropyl cellulose, and polyacrylic acid (hereinafter also referred to as "PAA") can be listed. The first binder preferably contains at least one of CMC and PAA, and more preferably contains CMC and PAA. CMC, MC and PAA may be in the form of an acid or in the form of a salt, preferably in the form of a salt. As the salt, alkali metal salts such as potassium and sodium can be listed.
[0065] The content of the first binder in the active material layer may be 0.5 to 5 parts by weight, 1 to 4 parts by weight, or 2 to 3 parts by weight relative to 100 parts by weight of the active material particles. When there are two or more first binders, the content of the first binder refers to the total amount thereof.
[0066] As for the active material layer, in addition to the active material particles, CNT and the first binder, a second binder other than the first binder and a conductive material other than CNT may also be included. In the case where the first binder includes at least one of CMC and PAA, or at least one of CMC and PAA, the second binder may include at least one of styrene butadiene rubber (SBR) and polyvinyl alcohol (PVA), preferably SBR. As conductive materials other than CNT, carbon materials such as carbon black (e.g., acetylene black, Ketjen black), coke, and activated carbon may be listed.
[0067] (Method for manufacturing negative electrode)
[0068] Figure 3 Flow chart showing the method for manufacturing a negative electrode of the embodiment. The method for manufacturing a negative electrode of the embodiment can manufacture a negative electrode for a secondary battery, and can also manufacture the present negative electrode. The method for manufacturing a negative electrode includes: a first step of preparing a slurry, and a second step of forming an active material layer of the negative electrode using the slurry ( Figure 3 The slurry includes active material particles, a first binder, CNTs, and water. The active material particles include metal particles and carbon particles.
[0069] As metal particles and carbon particles, the above-mentioned materials can be cited. As the first binder, the above-mentioned materials can be cited. As for CNT, the above-mentioned CNT can be cited, preferably SWCNT. The G / D ratio of CNT can be set to the range described above.
[0070] The slurry may further contain a second binder and may contain a conductive material other than CNTs. Examples of the second binder and the conductive material include the materials described above.
[0071] The solid content of the slurry prepared in the first step may be 35 to 55% by weight, 40 to 50% by weight, or 43 to 48% by weight.
[0072] The first step includes:
[0073] A step (1a) of obtaining a first kneaded body by kneading active material particles, a first binder, and water in a solid content range of 60 to 65% by weight;
[0074] A step (1b) of adding water to the first kneaded body and kneading the body so that the solid content is 50% by weight or less to obtain a second kneaded body; and
[0075] Step (1c) of obtaining a third kneaded body by kneading the second kneaded body and CNTs ( Figure 3 ).
[0076] In the manufacturing method of the negative electrode, the active material particles and the first binder are kneaded with a relatively large solid content to obtain a first mixed body (process (1a)), and the first mixed body is diluted to obtain a second mixed body (process (1b)). The first mixed body does not contain CNTs. The second mixed body has a relatively small solid content, so in process (1c), the shear force used to disperse the CNTs can be reduced. As a result, the load applied to the CNTs can be reduced by kneading in process (1c), so that the shortening of the length of the CNTs due to the shredding of the CNTs can be suppressed. As a result, the proportion of CNTs spanned between the active material particles can be increased, so that a good conductive path can be formed between the active material particles, and the cycle characteristics of the secondary battery can be improved. In addition, since the second mixed body with a relatively small solid content is kneaded with CNTs, an active material layer with a large proportion of the above-mentioned first CNTs relative to all CNTs can be formed.
[0077] The solid content in step (1a) (solid content of the first kneaded body) may be 61 to 65% by weight, 62 to 65% by weight, or 63 to 64% by weight. When the solid content in step (1a) is within the above range, the surface of the active material particles can be easily covered with the first binder.
[0078] Step (1a) may include: a step of dry-mixing the active material particles and the first binder to obtain a mixture; and a step of kneading the mixture and water in a range of 60 to 65% by weight of solid content. The solid content in the step of kneading the mixture and water may be 61 to 65% by weight, 62 to 65% by weight, or 63 to 64% by weight.
[0079] The solid content in step (1b) (solid content of the second kneaded product) may be 49 wt % or less, 48 wt % or less, 35 to 50 wt %, 40 to 49 wt %, or 43 to 48 wt %.
[0080] The first step may further include a step of kneading the third kneaded product with a second binder (hereinafter also referred to as “step (1d)”). In this case, it is preferred that the first binder is at least one of CMC and PAA, and the second binder is SBR.
[0081] The first step can be carried out using a stirrer having a stirring blade. Examples of the stirrer include a kneader and a homodisperser, which can be used alone or in combination. For example, a kneader can be used in steps (1a) and (1b), and a homodisperser can be used in steps (1c) and (1d).
[0082] There is no particular limitation on the rotation speed of the stirring blade in each step included in the first step. The rotation speed of the stirring blade in step (1a) may be 10 to 65 rpm, 20 to 60 rpm, or 30 to 55 rpm. The kneading time in step (1a) may be 10 to 200 min, 70 to 150 min, or 80 to 120 min.
[0083] The rotation speed of the stirring blade in step (1b) may be 5 to 50 rpm, 10 to 40 rpm, or 20 to 35 rpm. The kneading time in step (1b) may be, for example, 10 to 180 min, 20 to 150 min, or 25 to 120 min.
[0084] The rotation speed of the stirring blade in step (1c) may be 500 to 3000 rpm, 1000 to 2000 rpm, or 1200 to 1800 rpm. The kneading time in step (1c) may be, for example, 10 to 180 min, 20 to 150 min, or 25 to 100 min.
[0085] The rotation speed of the stirring blade in step (1d) may be 500 to 4000 rpm, 1000 to 3000 rpm, or 1500 to 2500 rpm. The kneading time in step (1d) may be, for example, 0.5 to 100 min, 1 to 60 min, or 3 to 30 min.
[0086] The second step is a step of forming an active material layer using the slurry prepared in the first step. The second step may include a step of applying the slurry on the negative electrode collector to form a coating layer, and drying the coating layer, and may further include a step of compressing the dried coating layer. As the negative electrode collector, the above-mentioned materials can be listed.
[0087] (Non-aqueous electrolyte secondary battery)
[0088] The non-aqueous electrolyte secondary battery of the present embodiment (hereinafter also referred to as "the present battery") comprises the present negative electrode, and generally comprises: an electrode body comprising the present negative electrode and a non-aqueous electrolyte. The present battery may have a battery case for accommodating the electrode body and the non-aqueous electrolyte. The battery case may comprise: an outer casing having an opening, and a sealing plate for sealing the opening. The outer casing and the sealing plate are preferably made of metal, and can be formed using aluminum, aluminum alloy, iron, or iron alloy, for example, can be formed using an aluminum laminated film. A resin sheet serving as an electrode holder may be configured between the electrode body and the outer casing.
[0089] The electrode body may include the present negative electrode, the positive electrode, and the separator. In the electrode body, the active material layer of the present negative electrode and the positive electrode active material layer of the positive electrode are opposite to each other via the separator. The electrode body may be a stacked type in which the present negative electrode, the positive electrode, and the separator are stacked, or a wound type in which a stacked body of the present negative electrode, the positive electrode, and the separator is wound.
[0090] The positive electrode generally has a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector is, for example, a metal foil made of aluminum materials such as aluminum and aluminum alloys. The positive electrode active material layer contains positive electrode active material particles, and may further contain a conductive material and a binder. Examples of positive electrode active material particles include layered or spinel lithium transition metal oxides (e.g., LiNiCoMnO2, LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi 0.5 Mn 1.5 O4, LiCrMnO4, LiFePO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) particles. The lithium transition metal oxide may be a lithium nickel cobalt manganese composite oxide (NCM). As the conductive material, for example, carbon materials such as fibrous carbon (CNT (SWCNT, DWCNT)), carbon black (for example, acetylene black, Ketjen black), coke, activated carbon, etc. may be listed. As the binder, polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), and SBR may be listed.
[0091] The spacer has a substrate, and a functional layer may be provided on at least one side of the substrate. The substrate may be a porous sheet such as a film or nonwoven fabric made of a resin such as polyethylene, polypropylene, polyester, cellulose, polyamide, etc. The substrate may have a single-layer structure or a multi-layer structure. As for the functional layer, for example, an adhesive layer and a heat-resistant layer may be listed, and one or both of these may be provided. As for the adhesive layer, for example, it may be formed by an adhesive. The heat-resistant layer may, for example, contain a filler and a binder.
[0092] The non-aqueous electrolyte preferably contains a supporting salt in a non-aqueous solvent such as an organic solvent. As supporting salts, LiPF6, LiBF4, LiClO4, LiFSO3, LiBOB (lithium bis(oxalate)borate) etc. can be listed. The non-aqueous electrolyte can include one or more supporting salts of these. As non-aqueous solvents, for example, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate (PC), butylene carbonate (BC), and diethyl carbonate (DEC) etc. can be listed. The non-aqueous electrolyte can include one or more non-aqueous solvents of these.
[0093] (Method for producing non-aqueous electrolyte secondary battery)
[0094] The manufacturing method of the battery includes: a step of manufacturing a negative electrode by the manufacturing method of the negative electrode. The manufacturing method of the battery may further include: a step of obtaining an electrode body using the negative electrode, the positive electrode, and the separator, and a step of housing the electrode body and the non-aqueous electrolyte in a battery case.
[0095] Example
[0096] Hereinafter, the present disclosure will be described in more detail with reference to Examples and Comparative Examples. Figures 4 to 7 These are scanning transmission electron microscope images (SEM images) of the surfaces of the active material layers of the negative electrodes obtained in Examples 1 and 2 and Comparative Examples 1 and 2, respectively.
[0097] [Example 1]
[0098] (Production of negative electrode (1))
[0099] As the carbon-based particles, graphite particles were used, and as the metal-based particles, particles of a composite of Si and C (SiC composite particles) were used. The average particle size D50 of the graphite particles was 17 μm, and the specific surface area (BET) of the graphite particles was 2.2 m 2 / g. The CNT had a G / D ratio shown in Table 1. Using a kneader (HIBISMIX 2P-1 manufactured by PRIMIX) and a homodisperser (ROBOMICX manufactured by PRIMIX) as a stirrer, a slurry (1) was prepared according to the following procedure.
[0100] First, carbon particles, metal particles, CMC as a first binder, and PAA are dry mixed to obtain a mixture. Next, water is added to the mixture so that the solid content is 65% by weight, the speed of the mixer is set to 50 rpm, and the mixture is kneaded for 90 minutes to obtain a first kneaded body (process (1a)). Water is further added to the first kneaded body so that the solid content is 48%, the speed of the mixer is set to 30 rpm, and the mixture is kneaded for 30 minutes to obtain a second kneaded body (process (1b)). CNT (a water-soluble paste with a solid content of 1% by weight) is added to the second kneaded body, the speed of the homogenizer is set to 1500 rpm, and the mixture is kneaded for 30 minutes to obtain a third kneaded body (process (1c)). SBR is added to the third kneaded body, the speed of the homogenizer is set to 1500 rpm, and the mixture is kneaded for 30 minutes to obtain a slurry (1) (process (1d)). The mixing ratio of the slurry (1) was graphite particles: SiC composite particles: CNT: CMC: PAA: SBR = 91:9:0.05:1:1:1 (weight ratio).
[0101] The slurry (1) obtained above was applied to both sides of a copper foil with a thickness of 8 μm as a negative electrode current collector, dried, and compressed to obtain a negative electrode (1). The unit area mass (unit area mass of both sides combined) of the active material layer of the negative electrode (1) was 195 g / m 2 The thickness of the active material layer (per single side) was 130 μm, and the packing density of the active material layer was 1.52 g / cc. The SEM image of the surface of the active material layer of the negative electrode (1) is shown in Figure 4 The active material layer of the negative electrode (1) includes CMC and PAA (first binder) that cover at least a portion of the surface of the active material particles and do not contain CNTs, and includes: CNTs (first CNTs) covering the surfaces of the CMC and PAA, and CNTs (second CNTs) bridging between two active material particles.
[0102] (Production of positive electrode)
[0103] Lithium nickel cobalt manganese composite oxide (NCM) as positive electrode active material particles, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder are used in a ratio of positive electrode active material particles: AB: PVdF = 100: 1: 1 (weight ratio), and they are mixed with N-methylpyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry is applied on an aluminum foil with a thickness of 15 μm as a positive electrode collector, dried, and compressed to obtain a positive electrode.
[0104] (Fabrication of non-aqueous electrolyte secondary battery)
[0105] Leads are installed on the negative electrode and the positive electrode obtained above, and the negative electrode and the positive electrode are stacked via a separator to obtain an electrode body. The electrode body is inserted into an outer casing composed of aluminum laminate sheets, and a non-aqueous electrolyte is injected. The opening of the outer casing is sealed to obtain a test battery (laminated body battery) (1). As for the non-aqueous electrolyte, a product is used in which LiPF6 as a lithium salt is dissolved at a concentration of 1 mol / L in a mixed solvent containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of EC:EMC:DMC=20:40:40.
[0106] [Example 2]
[0107] (Preparation of negative electrode (2))
[0108] A negative electrode (2) was prepared by the same procedure as in Example 1 except that CNTs having the G / D ratio shown in Table 1 were used. A SEM image of the surface of the active material layer of the negative electrode (2) is shown in FIG. Figure 5The active material layer of the negative electrode (2) includes CMC and PAA (first binder) that cover at least a portion of the surface of the active material particles and do not contain CNTs, and includes: CNTs (first CNTs) covering the surfaces of the CMC and PAA, and CNTs (second CNTs) bridging between two active material particles.
[0109] (Fabrication of non-aqueous electrolyte secondary battery)
[0110] A test cell (2) was obtained by the same procedure as in Example 1 except that the negative electrode (2) was used instead of the negative electrode (1).
[0111] [Comparative Example 1]
[0112] (Fabrication of negative electrode (c1))
[0113] The carbon-based particles and metal-based particles used in Example 1 were dry-mixed with CMC and PAA as the first binder to obtain a mixture. Next, CNT (a water-soluble paste with a solid content of 1% by weight) and water having a G / D ratio shown in Table 1 were added to the mixture so that the solid content was 64% by weight, and the speed of the kneader was set to 50 rpm, and the kneading was performed for 90 minutes. Then, water was further added, the speed of the kneader was set to 30 rpm, and after kneading for 30 minutes, SBR was added as the second binder, the speed of the kneader was set to 30 rpm, and the kneading was performed for 5 minutes to obtain a slurry (c1) with a solid content of 46% by weight. The mixing ratio of the slurry (c1) was graphite particles: SiC composite particles: CNT: CMC: PAA: SBR = 91:9:0.05:1:1:1 (weight ratio).
[0114] A negative electrode (c1) was obtained by the same procedure as in Example 1 except that slurry (c1) was used instead of slurry (1). A SEM image of the surface of the active material layer of the negative electrode (c1) is shown in FIG. Figure 6 In the active material layer of the negative electrode (c1), a mixture of CNT and a binder (CMC and PAA) covers the surface of the active material particles and bridges between two active material particles.
[0115] (Fabrication of non-aqueous electrolyte secondary battery)
[0116] A test cell (c1) was obtained by the same procedure as in Example 1 except that the negative electrode (c1) was used instead of the negative electrode (1).
[0117] [Comparative Example 2]
[0118] (Production of negative electrode (c2))
[0119] A negative electrode (c2) was prepared by the same procedure as in Comparative Example 1 except that CNTs having the G / D ratio shown in Table 1 were used. A SEM image of the surface of the active material layer of the negative electrode (c2) is shown in FIG. Figure 7 In the active material layer of the negative electrode (c2), a mixture of CNT and a binder (CMC and PAA) covers the surface of the active material particles and bridges between two active material particles.
[0120] (Fabrication of non-aqueous electrolyte secondary battery)
[0121] A test cell (c2) was obtained by the same procedure as in Example 1 except that the negative electrode (c2) was used instead of the negative electrode (1).
[0122] [Determination of G / D ratio of CNT]
[0123] The CNT dispersion was distributed (distributed) on a cover glass, and a Raman microscope (manufactured by Horiba, Ltd.) was used to irradiate a laser with an excitation wavelength of 532 nm in a range of 300 μm in diameter to obtain a Raman spectrum. -1 The maximum peak intensity in the range of 1300 to 1400 cm -1 The maximum peak intensity in the range of was defined as D, and the G / D ratio was calculated. The results are shown in Table 1.
[0124] [Determination of average CNT length and CNT ratio]
[0125] (Acquisition of SEM images)
[0126] The surface of the active material layer of the negative electrode was confirmed by SEM imaging at an accelerating voltage of 1 kV and a field of view of 9×7 μm using a scanning transmission electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation).
[0127] (Determination of the average length of CNT)
[0128] Using image software, the CNT in the above SEM image is divided into lines, the perimeter of the line is measured, and half of the value is used as the length of the CNT. As far as CNT is concerned, it has an extremely long aspect ratio relative to the diameter, so the width of the line that affects the perimeter can be ignored. For all CNTs in the above SEM image, the length of the CNT is determined, and the value obtained by averaging it is set as the average length of the CNT. The results are shown in Table 1.
[0129] (Determination of CNT ratio)
[0130] For all CNTs in the SEM image obtained above, the ratio [%] of CNTs not mixed with CMC and PAA (first binder) (CNT ratio [%]) was calculated according to the following formula. The results are shown in Table 1.
[0131] CNT ratio [%] = (area of CNTs not mixed with the first binder in the SEM image / area of all CNTs in the SEM image) × 100
[0132] [Evaluation of cycle characteristics (1)]
[0133] Under the environment of 25°C, the test battery was charged to 4.2V by constant current and constant voltage charging (CCCV) with a current value of 0.2C (cut off at 0.1C), and then discharged to 2.5V with a current value of 0.33C (CC discharge). This charge and discharge was regarded as one cycle, and the charge and discharge were repeated N [cycles]. For the test batteries obtained in Example 1 and Comparative Example 1, the number of charge and discharge repetitions N was 100 cycles, and for the test batteries obtained in Example 2 and Comparative Example 2, the number of charge and discharge repetitions N was 150 cycles. According to the following formula, the discharge capacity of the Nth cycle relative to the discharge capacity of the first cycle was calculated as the capacity retention rate [%]. The results are shown in Table 1.
[0134] Capacity retention rate [%] = (discharge capacity at the Nth cycle / discharge capacity at the 1st cycle) × 100
[0135]
Table 1
[0136] Example 1 Example 2 Comparative Example 1 Comparative Example 2 negative electrode (1) (2) (c1) (c2) Slurry (1) (2) (c1) (c2) CNT G / D Ratio 11.81 69.19 11.81 69.19 Average length [μm] 2.11 1.98 1.64 1.57 <![CDATA[Ratio of CNT *1 [%]]]> 93.9 87.6 11.3 52.0 Test battery (1) (2) (c1) (c2) Capacity maintenance rate [%] 72.5 96.46 71.4 96.25
[0137] *1: Ratio of CNTs not mixed with the first binder in the SEM image
[0138] Although the embodiments of the present invention have been described, the embodiments disclosed this time should be considered to be illustrative in all aspects and not restrictive. The scope of the present invention is indicated by the claims, and it is intended to include all modifications within the meaning and scope equivalent to the claims.
Claims
1. Negative electrode, which is a negative electrode for non-aqueous electrolyte secondary batteries. The invention comprises an active material layer including active material particles, carbon nanotubes, and a first binder, The active material particles include metal-based active material particles and carbon-based active material particles. The average length of the carbon nanotubes determined by analysis of a scanning transmission electron microscope image of the active material layer is 1.5 μm or more, At least a portion of the first binder covers at least a portion of the surface of the active material particle in a state where the first binder is not mixed with the carbon nanotubes. The carbon nanotubes include: first carbon nanotubes attached to the first binder in a manner of covering the first binder, and second carbon nanotubes spanning between two active material particles, and the first binder covers the surface of the active material particles in a state of not being mixed with the carbon nanotubes.
2. The negative electrode according to claim 1, wherein The ratio of the carbon nanotubes not mixed with the first binder to the total amount of the carbon nanotubes in the active material layer, as determined by analyzing the scanning transmission electron microscope image of the active material layer, is greater than 60%.
3. The negative electrode according to claim 1, wherein The metal-based active material particles include particles of one or more selected from Si, SiOx, and a composite of Si and C.
4. The negative electrode according to claim 1, wherein The metal-based active material particles include particles of a composite of Si and C.
5. The negative electrode according to claim 1, wherein The carbon nanotubes are single-layer carbon nanotubes.
6. The negative electrode according to claim 1, wherein The G / D ratio of the carbon nanotubes is 80 or less.
7. The negative electrode according to claim 1, wherein The first binder is at least one of carboxymethyl cellulose and polyacrylic acid.
8. The negative electrode according to claim 7, wherein The active material layer includes a second binder different from the first binder, The second binder includes styrene butadiene rubber. 9 . A nonaqueous electrolyte secondary battery comprising the negative electrode according to claim 1 .
10. A method for producing a negative electrode, which is a method for producing a negative electrode for a non-aqueous electrolyte secondary battery. include: a first step of preparing a slurry, and a second step of forming an active material layer of the negative electrode using the slurry, The slurry comprises: active material particles, a first binder, carbon nanotubes, and water. The active material particles include metal-based active material particles and carbon-based active material particles. The first step includes: a step (1a) of obtaining a first mixed body by kneading the active material particles, the first binder, and water in a solid content range of 60 to 65 weight %; a step (1b) of obtaining a second mixed body by adding water to the first mixed body and kneading in a solid content range of less than 50 weight %; and a step (1c) of obtaining a third mixed body by kneading the second mixed body and the carbon nanotubes.
11. The method for manufacturing a negative electrode according to claim 10, wherein: The first binder is at least one of carboxymethyl cellulose and polyacrylic acid, The first step further includes a step of kneading the third kneaded body with a second binder. The second binder includes styrene butadiene rubber.
12. The method for manufacturing a negative electrode according to claim 10, wherein: The step (1a) comprises: a step of dry-mixing the active material particles and the first binder to obtain a mixture; and The step of kneading the mixture and water so that the solid content is within the range of 60 to 65% by weight.
13. The method for manufacturing a negative electrode according to claim 10, wherein: The metal-based active material particles include particles of one or more selected from Si, SiOx, and a composite of Si and C.
14. The method for manufacturing a negative electrode according to claim 10, wherein: The first binder is at least one of carboxymethyl cellulose and polyacrylic acid.
15. The method for manufacturing a negative electrode according to claim 10, wherein: The G / D ratio of the carbon nanotubes is 80 or less.
16. A method for manufacturing a non-aqueous electrolyte secondary battery, comprising: A step of manufacturing a negative electrode by the method for manufacturing a negative electrode according to any one of claims 10 to 15.
Citation Information
Patent Citations
Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
JP2021099955A